1989
DOI: 10.1128/iai.57.10.2984-2990.1989
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion to and invasion of HEp-2 cells by Campylobacter spp

Abstract: Twenty-one isolates were tested for their ability to adhere to and invade HEp-2 cells in vitro. Of the 21 organisms tested, 2 did not invade the HEp-2 cells, and 1 of these did not adhere to the epithelial cells. Campylobacterjejuni clinical isolates were more invasive than the nonclinical strains that were tested. When HEp-2 cells were treated with cytochalasin B, the invasiveness of C. jejuni was reduced, indicating active participation of the host cell in the uptake of these organisms. The number of intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(72 citation statements)
references
References 41 publications
5
67
0
Order By: Relevance
“…Intestinal epithelial NOD1 and NOD2 gene expression is not modulated in response to C. jejuni Bacterial adherence to and subsequent invasion of the IEC is a well established early event in C. jejunimediated disease pathogenesis (Konkel and Joens, 1989;Szymanski et al, 1995;Monteville et al, 2003).…”
Section: Intracellular C Jejuni Bacterial Component(s) Play An Impormentioning
confidence: 99%
“…Intestinal epithelial NOD1 and NOD2 gene expression is not modulated in response to C. jejuni Bacterial adherence to and subsequent invasion of the IEC is a well established early event in C. jejunimediated disease pathogenesis (Konkel and Joens, 1989;Szymanski et al, 1995;Monteville et al, 2003).…”
Section: Intracellular C Jejuni Bacterial Component(s) Play An Impormentioning
confidence: 99%
“…The adherence and invasion assays were performed by the method of Konkel and Joens [21] with some modi¢cation. Brie£y, 100 Wl of bacterial suspension, containing CFU approximately 100 times higher than cell number, was inoculated into duplicate wells of a 24-well tissue culture plate containing semicon£uent monolayers of INT-407 cells.…”
Section: Adherence and Invasion Assaymentioning
confidence: 99%
“…However. C. jejuni and 0. coli have recently been shown to be naturally transformable (Wang and Taylor, 1990), although this observation has been only of limited use in terms of genetic exploifation of the genus, Campylobaoter diarrhoea most often presents with symptoms typical of an invasive disease (Skirrow and Blaser, 1992), Consistent with this, several kiboratories have reported that some Campylobacter strains can invade a variety of eukaryotic cells in culture at relatively low levels by a microfilament (MF)-dependent mechanism (Konkei and Joens. 1989;Konkel et ai, 1992); more recently, a higher level microtubule (MT)-dependent system has been described for other strains, including C. jejuni 8^-^76 (Oelschlaegor et ai.…”
Section: Introductionmentioning
confidence: 96%